Gravity Prediction Method and the Application of Full-Space Tunnels in the Deep Extension of High-Density Vertical Orebodies - Wang, Jiyu; Han, Runsheng; Li, Wenyao; Cheng, Ruihong (Frontiers in Earth Science, 2022)
A full-space tunnel gravity prediction method for evaluating the deep extension of high-density vertical orebodies has been developed based on the significant density differences between surrounding rocks and their characteristics as large-scale orebodies. This method uses the residual gravity anomaly parameters in the tunnel to determine whether the orebody is upright based on the symmetry of the anomaly. Moreover, it identifies the deep extensional characteristics of high-density upright orebodies based on the positive and negative anomalies. This method has characteristics such as strong anti-interference ability, slight influence from the terrain, and high detection accuracy. It has produced promising outcomes in the detection of deep, concealed orebodies in the Huangshaping skarn-type tin–tungsten polymetallic deposit located in southern Hunan. This method not only resolves the problem of rapid identification of the deep extension of single-hole high-density orebodies and provides reference basis for deep exploration but also proposes a new method for mineral resource evaluation.